Elucidation of drug resistance mutations in Mycobacterium tuberculosis isolates from North India by whole-genome sequencing. (March 2020) - Sethi, Sunil; Hao, Yuhan; Brown, Stuart M.; Walker, Timothy; Yadav, Rakesh; Zaman, Kamran; Aggarwal, Ashutosh Nath; Behera, Digambar
Highlights: Whole-genome sequencing of Mycobacterium tuberculosis (MTB) isolates. 21 isolates (72.4%) were multidrug-resistant (MDR) and 1 (3.4%) was extensively-drug resistant (XDR-TB). The most common mutations observed for isoniazid and rifampicin resistance were katG (S315T) and rpoB (S450L), respectively. The most common mutations observed for ofloxacin and kanamycin resistance were gyrA (A90V) and rrs (A1401G), respectively. The isolates belonged mainly to lineages 2 and 3, with most MDR-TB among lineage 2 isolates. Abstract: Objectives: Rapid diagnosis of drug-resistant tuberculosis (TB) is required for better patient management and treatment outcomes. Whole-genome sequencing (WGS) can be used to detect single nucleotide polymorphisms (SNPs) and deletions/insertions that are responsible for most Mycobacterium tuberculosis drug resistance. WGS is being performed at scale in high-income countries, but there are limited reports of its use in India. Methods: In this study, 33 clinical M. tuberculosis isolates from the Mycobacterial Repository in Chandigarh underwent WGS. Phenotypic drug susceptibility testing was performed according to World Health Organization (WHO) recommendations. Four isolates were excluded from the analysis due to culture contamination or mislabelling during the study. Results: Among the remaining 29 isolates, 21 (72.4%) were multidrug-resistant TB (MDR-TB) and 1 (3.4%) was extensively-drug resistant TB (XDR-TB). The most common mutations observed for isoniazid, rifampicin, ofloxacin and kanamycin resistance were katG (S315T), rpoB (S450L), gyrA (A90V) and rrs (A1401G), respectively. The isolates mainly belonged to lineages 2 and 3, with most MDR-TB among lineage 2 isolates. Conclusion: WGS of M. tuberculosis isolates allows the detection of drug resistance to all drugs in a single test and also provides insight into the evolution and drug-resistant TB.